2023
DOI: 10.1111/myc.13604
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pulmonary mucormycosis in subjects with diabetes mellitus—A case‐control study

Abstract: Background: Factors associated with pulmonary mucormycosis (PM) among subjects with diabetes mellitus (DM) remain unclear. Following the coronavirus disease (COVID-19)-associated mucormycosis outbreak in India, specific environmental exposures (especially cattle dung exposure) were proposed as possible aetiology. We hypothesized that environmental factors are associated with PM. We compared subjects with DM with (cases) and without PM (controls). Methods:In this case-control study, for each PM case, we include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Further, in a recent case-control study, we compared 39 cases of pulmonary mucormycosis in diabetes mellitus with 199 controls with diabetes mellitus (119 from the community and 80 from the hospital) without pulmonary mucormycosis [ 40 ]. We elicited a detailed history of various environmental exposures, including farming practices, place of stay, cattle handling, use of cow-dung cakes as fuel, and several others.…”
Section: Is There Truth To the Claim Of Cam Due To Cow Dung Exposure?...mentioning
confidence: 99%
“…Further, in a recent case-control study, we compared 39 cases of pulmonary mucormycosis in diabetes mellitus with 199 controls with diabetes mellitus (119 from the community and 80 from the hospital) without pulmonary mucormycosis [ 40 ]. We elicited a detailed history of various environmental exposures, including farming practices, place of stay, cattle handling, use of cow-dung cakes as fuel, and several others.…”
Section: Is There Truth To the Claim Of Cam Due To Cow Dung Exposure?...mentioning
confidence: 99%
“…It was speculated that changes in the immune landscape due to COVID‐19 or mechanisms seen in influenza‐associated pulmonary aspergillosis (IAPA) might also be operative in the development of mucormycosis post‐COVID‐19 4 . Pulmonary mucormycosis is a life‐threatening opportunistic fungal infection that typically affects immunocompromised patients with haematological malignancies or neutropenia 5,6 . The clinical presentation ranges from acute to subacute, depending on the host's immune status, with a mortality rate of 57.1% 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation ranges from acute to subacute, depending on the host's immune status, with a mortality rate of 57.1% 7 . The immunological status of patients who develop pulmonary mucormycosis post SARS‐CoV‐2 infection is unclear 6,8 . Few studies from India highlighted the clinical and immunological characteristics observed among CAPM patients 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations